Dynamic decisions energy PIVOT, Adaptive Moves, Winning BOUnCE - Barcelona, Ricardo G.; Heukamp, Franz (London, United Kingdom World Scientific, 2023)
Dynamic Decisions highlights how some managers and policymakers sleepwalk into decision paralysis. Strategically, they partly recognise their world is changing radically as energy systems transition. In deciding what to invest in, they default to rewarding the predictable and proven, often misdiagnosing the ignored risks of innately ambiguous markets. To remedy this, the author frames ambiguity as a source of opportunity. As extant advantages obsolesce, new entrants could disrupt to gain dominance. Some managers could repurpose, reframe, and reconfigure their resources and processes to create tomorrow's profitable niches today. To profit from these emerging business landscapes, managers can PIVOT and BOUnCE to win by transitioning into a dynamic mindset. Endowed with a creative mind to innovate, humans could reshape their firms and their societies. Armed with these capabilities, albeit partial, managers could choose to adapt responsive strategic actions that are tangible, actionable, and achievable, with policy sustaining societal benefits by expanding people's access to opportunities."
Chapter 1 From Impasse to PIVOT -- Chapter 2 Policy and Managerial Actions -- Chapter 3 Articulate a Purpose -- Chapter 4 Bounded Possibilities -- Chapter 5 Calibrate -- Chapter 6 Take Actions to De-risk -- Chapter 7 Cost of Energy -- Chapter 8 Levers of Value -- Chapter 9 Price Taker -- Chapter 10 Oligopolistic Rivalries -- Chapter 11 PIVOT and BOUnCE to Profit. -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: Management -- Technological innovations; Business enterprises -- Technological innovations; Organizational change; Strategic planning; Creative ability in business